Improved millets cultivation for enhancing farmers’ income in rainfed areas - Chapke, Rajendra R; Tonapi, Vilas A (Indian Farming, 2019)
rainfed agriculture using location-specific improved production technology with diversificationapproach. It requires synergy among technologies, marketing systems, input supplies, credit, policiesand concerned institutions to achieve the goal of doubling farmers’ income emphasizing plough toplate transition.